2015
DOI: 10.1093/ofid/ofv083
|View full text |Cite
|
Sign up to set email alerts
|

Host Characteristics and Bacterial Traits Predict Experimental Virulence for Escherichia coli Bloodstream Isolates From Patients With Urosepsis

Abstract: Virulence assessment of 67 E. coli urosepsis isolates in a murine sepsis model in relation to host and bacterial characteristics suggested that host compromise, including older age and urinary tract abnormalities, allows comparatively low-virulence E. coli strains to cause urosepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 24 publications
10
108
1
Order By: Relevance
“…A previous study involving a murine sepsis model found that, among human urosepsis isolates, a group B2 background and specific virulence genes, including several that here were associated with ExPEC status among chicken-source E. coli isolates, were significantly predictive of experimental morbidity and lethality in mice (27). A similar in vivo assessment of the present isolates would be of interest, to confirm that the molecular markers detected here predict extraintestinal virulence in a mammalian host.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A previous study involving a murine sepsis model found that, among human urosepsis isolates, a group B2 background and specific virulence genes, including several that here were associated with ExPEC status among chicken-source E. coli isolates, were significantly predictive of experimental morbidity and lethality in mice (27). A similar in vivo assessment of the present isolates would be of interest, to confirm that the molecular markers detected here predict extraintestinal virulence in a mammalian host.…”
Section: Discussionsupporting
confidence: 74%
“…This suggests that, to the extent that the molecular markers that we used predict virulence potential in humans (27), label claims such as those that we studied cannot be used to guide selective purchasing choices for consumers who wish to avoid foodborne exposure to virulent E. coli strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, to the extent that virulence gene content predicts actual virulence potential (27), strains with more extensive virulence gene profiles may be more likely to cause infections and/or to cause more severe infections. As such, the H30 expansion may have both enlarged the resistant population and made it more aggressive, thereby resulting in the double threat of more severe infections that also are harder to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Minimum inhibitory concentration (MIC) results were interpreted according to the Clinical Laboratory and Standards Institute criteria (Clinical and Laboratory Standards Institute, 2013). In addition, isolates were assessed molecularly for bla CTX-M-15 , major E. coli phylogenetic group (phylogroup) (Clermont et al, 2013), ST or ST complex (STc; as determined by fumC-fimH typing (Weissman et al, 2012), full or partial MLST (Maiden et al, 1998), or STc-specific PCR assays Johnson et al, 2009;Matsumura et al, 2012)), membership in the ST131-H30 clonal subset or its sublineage ST131-H30Rx (Banerjee et al, 2013), O type (O16 and O25b only) (Johnson et al, 2014), and extended virulence genotype (for 50 markers) (Johnson et al, 2015). Resistance scores were defined as the number of antibiotic classes to which an isolate exhibited resistance.…”
Section: Laboratory Analysismentioning
confidence: 99%